2020
DOI: 10.1002/ame2.12142
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the structure and function of endomucin

Abstract: Endomucin is a type I integral membrane glycoprotein, which is expressed in venous and capillary endothelial cells. It consists of 261 amino acids with an extracellular domain that is highly O‐glycosylated at serine and threonine residues and has several potential N‐glycosylation sites. Endomucin plays an important role in biological processes such as cell interaction, molecular cell signaling, angiogenesis and cell migration, and in recent years it has also been identified as an anti‐adhesion molecule and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…EMCN is a heavily O-glycosylated single-transmembrane sialomucin, expressed by venous and capillary rather than arterial endothelium. 30 The Western blotting assays showed that the iPSC-ECs under both normoxia and hypoxia expressed EMCN (Figure S2), which indicated that iPSC-ECs were more like venous and capillary endothelium. CXCR4 acts as the receptor for stromal cell-derived factor 1 (SDF1), which mediates the bone marrow homing of peripheral or transplanted CXCR4 + HSPCs.…”
Section: Resultsmentioning
confidence: 99%
“…EMCN is a heavily O-glycosylated single-transmembrane sialomucin, expressed by venous and capillary rather than arterial endothelium. 30 The Western blotting assays showed that the iPSC-ECs under both normoxia and hypoxia expressed EMCN (Figure S2), which indicated that iPSC-ECs were more like venous and capillary endothelium. CXCR4 acts as the receptor for stromal cell-derived factor 1 (SDF1), which mediates the bone marrow homing of peripheral or transplanted CXCR4 + HSPCs.…”
Section: Resultsmentioning
confidence: 99%
“…5k-l ). Endomucin (Emcn) is an integral membrane glycoprotein expressed in cECs and vECs 74 that modulates VEGF-induced angiogenesis in the developing retina 75 . DE analysis by scRNAseq revealed that Emcn expression was upregulated in EAE vECs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is further interesting to note that the expression of EMCN in the main capillary population increases slightly in time, unlike CD31 expression. EMCN is strongly involved in neovascularization [30], while CD31 plays an important role in intercellular junctions and the mechanisms of leukocyte transendothelial migration [31,32], especially for neutrophils and monocytes. When CD31 decreases, the migration of these cells through the capillaries to the tissues decreases [33].…”
Section: Discussionmentioning
confidence: 99%